Ethnographic Research: Potential of Local Culinary as a Tourist Attraction Object in Simalungun Regency, Indonesia - Indra, Rama; Sibarani, Robert; Revida, Erika; Rujiman (Cattleya Darmaya Fortuna, 2024)
The objectives of this research include exploring the potential of local culinary as a tourist attraction in four Destination Tourist Objects (ODTW), namely Haranggaol, BIS, Sibaganding, and Parapat in Simalungun Regency, Indonesia. The interconnection between food and tourism is currently growing. This research is an ethnographic study to support the acceleration of culinary tourism development in Simalungun Regency. Data were collected through observation and ethnographic interviews with 3 informants, namely key informants, main informants, and supporting informants. Using selective observation and contrasting questions, several contrasting dimensions among the residents of a domain can be identified (for example, we will know that the main foods are